Performance of a HAWT rotor with a modified blade configuration - Khan, Tabrej; Singh, Balbir; Hameed Sultan, Mohamed Thariq; Ahmad, Kamarul Arifin (Universiti Putra Malaysia Press, 2022)
As the world focuses more on clean and green Earth, wind energy plays a significant role. Wind energy is a renewable source of energy that can cope with the ongoing global fossil fuel crisis. The wind energy converters like wind turbines have been studied a lot in terms of design and performance. The current work includes analyzing the output effects of a horizontal axis wind turbine (HAWT) with a modified blade configuration at specific wind speeds. A numerical investigation is carried out using two different numerical software on the chosen airfoil used in blade design validated with the analysis carried out in openloop wind tunnels. The study is divided into two phases: first, the selected airfoil is tested experimentally and using CFD, and then the findings are compared to those of the University of Illinois Urbana Champaign wind tunnel tests at low Reynolds numbers. The second phase includes the numerical analysis based on the blade element momentum method and nonlinear lifting line simulations of modified blade design at high Reynolds number. The numerical results of rotor performance analysis have been compared to existing experimental results. The findings of all numerical investigations agree with those of the experiments. An optimal value of the power coefficient is obtained at a particular tip speed ratio close to the desired value for large wind turbines. For maximum power, this study investigates the optimum pitch angle. The work demonstrated the improved HAWT rotor blade design to produce better aerodynamic lift and thus improve performance.